Circulating tissue inhibitor of matrix metalloproteinase-1 is associated with aldosterone-induced diastolic dysfunction. Issue 9 (September 2015) - Hung, Chi-Sheng; Chou, Chia-Hung; Wu, Xue-Ming; Chang, Yi-Yao; Wu, Vin-Cent; Chen, Ying-Hsien; Chang, Yuan-Shian; Tsai, Yao-Chou; Su, Ming-Jai; Ho, Yi-Lwun; Chen, Ming-Fong; Wu, Kwan-Dun; et al.
<x xml:space="preserve">Abstract</x> Objective: To test if collagen markers are associated with aldosterone-induced diastolic dysfunction. Background: Although primary aldosteronism is associated with more prominent cardiac remodeling and diastolic dysfunction, the reversibility of diastolic function is unclear. In addition, there is no known biomarker associated with aldosterone-induced diastolic dysfunction. Methods: We enrolled 27 patients with aldosterone-producing adenoma (APA) preparing for adrenalectomy, and 27 patients with essential hypertension prospectively from October 2006 to March 2010 at a tertiary referral center. Plasma matrix metalloproteinase-2 (MMP-2) and tissue inhibitor of matrix metalloproteinase-1 (TIMP-1) were measured, and echocardiography including tissue Doppler images was performed in both groups and 1 year after receiving adrenalectomy in the APA group. Results: The baseline plasma TIMP-1 level (88.4 ± 38.7 vs. 63.6 ± 32.5 ng/ml; P = 0.014), left ventricular mass index (LVMI), and E/E' ratio (11.5 ± 2.9 vs. 9.0 ± 2.1; P < 0.001) were significantly higher in the APA group. The baseline plasma TIMP-1 level significantly correlated with the E/E' ratio, LVMI, interventricular septum, and left atrial diameter. The plasma MMP-2 level did not correlate with the left ventricular structure parameters, except for interventricular septum thickness. After adrenalectomy, LVMI and E/E' ratio improved significantly. The postadrenalectomy plasma TIMP-1 levels, but not MMP-2 levels, also decreased. The change of plasma TIMP-1 levels was negatively associated with the postadrenalectomy E/E' ratio after adjustment for age, sex, BMI, and mean blood pressure (β-coefficient = − 3.6, P = 0.004). Conclusion: Excess of aldosterone induces cardiac diastolic dysfunction, which is reversible by adrenalectomy. TIMP-1 is associated with the aldosterone-induced diastolic dysfunction.